Faktor-faktor yang mempengaruhi Opini Audit Going concern: Ukuran Perusahaan, Profitabilitas dan Opini Audit tahun sebelumnya - Sahidal Sahidal; Cris Kuntadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article discusses the variables that influence going concern audit opinions, including company size, profitability and previous year's audit opinion. Find out Finding out what elements influence the going concern audit opinion of a financial company is the goal here. This research uses qualitative research methods and library sources. This research investigates the relationship between the length of time between an audit opinion and receipt of a going concern opinion, as well as company size and profitability. This article's literature study reveals three things regarding going concern audit opinions: 1) company size is the main factor; 2) company profitability is an important factor; and 3) annual audit opinion is a previously influential factor.